2012
DOI: 10.4103/2230-973x.106981
|View full text |Cite
|
Sign up to set email alerts
|

Formulation strategies for drug delivery of tacrolimus: An overview

Abstract: Tacrolimus (FK 506) is a potent macrolide lactone immunosuppressive agent used for prophylaxis of organ rejection after transplantation and graft-versus-host disease after bone marrow transplantation in patients. Moreover, tacrolimus is a drug of choice in the treatment of atopic dermatitis for decreasing side effects associated with the use of topical corticosteroids. In spite of its success in ensuring graft survival, therapeutic use of tacrolimus is complicated due to its narrow therapeutic index (between 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 42 publications
1
39
0
3
Order By: Relevance
“…When used with hydrophilic substances such as liposomes, tacrolimus becomes highly soluble. 11 Pharmacokinetic study revealed that the use of liposomes as a delivery vehicle increased endocytosis while decreasing systemic exposure and vehicle related toxicity in comparison to non-encapsulated tacrolimus in rats. 12, 13 …”
Section: Introductionmentioning
confidence: 99%
“…When used with hydrophilic substances such as liposomes, tacrolimus becomes highly soluble. 11 Pharmacokinetic study revealed that the use of liposomes as a delivery vehicle increased endocytosis while decreasing systemic exposure and vehicle related toxicity in comparison to non-encapsulated tacrolimus in rats. 12, 13 …”
Section: Introductionmentioning
confidence: 99%
“…The main focus of formulating the poorly aqueous soluble drug is to present the drug in its molecular form to the absorbing surface, that is, gut mucosa. Any intrinsic or extrinsic factor triggering crystallization of the drug in the formulation can impact an overall absorption and thereby bioavailability of the drug, which is of particular concern to a drug like tacrolimus possessing a narrow therapeutic index (5–15 μg/mL) . Sub‐potent dose of tacrolimus can increase the potential of a graft rejection, whereas overdose can cause dose‐dependent neuro/nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Tacrolimus is classified as a class II drug according to the biopharmaceutical classification system (12). Tacrolimus exhibits poor aqueous solubility, P-gp efflux, and extensive presystemic metabolism resulting in low bioavailability following oral administration (13)(14)(15)(16). The reported mean bioavailability is approximately 21% with large intersubject variability.…”
Section: Introductionmentioning
confidence: 99%